Injusto penal restaurável: análise da ingerência penal na perspectiva da proteção às vítimas de crimes - Santos, Celeste Leite dos (2019)
The goal of this dissertation is to propose the concept of restorable unfair criminal, integrating the institute of Restoration with the criminal science. This dissertation systemically analyses the criminal interference made by the State, covering the full analysis of the criminal, criminal procedure and criminal enforcement law. The perspective of protection to the victim of crimes aims to analyze the criminogenic phenomenon in its entirety, in other words, surpassing the established binary model established in the State / Offender relationship. Without neglecting the subsidiary nature of criminal law, the incorporation of the restorative criminal injustice aims to address the need for adoption of the perspective of the victim in the theory of crime, in which the attention is fully focused on the aggressor. It is of paramount importance to aggregate preventive public policies related to the phenomenon of victimization to the delinquency studies, given the evident connection between them. The feelings inherent to the victimization, which are today foisted to certain direct, indirect or collective victim (acting in), may give rise to the victim's assumption of the role of aggressor (acting out), which generates endless cycles of violence in our society. We are all both victims and aggressors at the same time. Breaking this addicted model is one of the greatest challenges to social pacification in this century. The unjust restorable criminal category allows us to understand crime as an offense to the protected legal property, which causes trauma, violence and social conflicts. Ad argumentandum, the perpetuation of violence in the society encompasses the criminal response that are not always appropriate to the aggressor neither for the victim. In victimological terms, the cycle of violence involves two parties, aggressor and victim, which is why it proposes the integrated treatment of the “criminal couple”. Our Constitution contains explicit and implicit values that allow us to conclude that, along with the individual guarantees inherent to the freedom of the individuals before the State (eg right to the due criminal procedure), and the guidelines of criminalization of conducts that hinder or prevent the material equality of citizens (eg warrants of criminalization of any form of discrimination on grounds of sex, etc.), we have the duties of solidarity (eg free, fair and solidary society)